Geological controls on large landslides: evidence from the 2024 Wayanad event, India - B. G. Aswathi; Y. Anilkumar; K. S. Sajinkumar; V. K. Krishnapriya; Ali P. Yunus; Mubassira Mushrifa; Durga Prasanna Mohanty (Landslides, 2026)

Genome-wide identification of genetic determinants for gall midge resistance in rice using genic markers - Basana Gowda Gadratagi; Lopamudra Mandal; Rameswar Prasad Sah; Anilkumar C.; Guru-Pirasanna-Pandi G.; Naveenkumar B. Patil; Nandini Sahu; Muhammed Azharudheen T. P.; Sasmita Behera; Prakash Chandra Rath; Shyamaranjan Das Mohapatra (Journal of Applied Genetics, 2026)

Long-term Observations of Aerosol Optical Properties Over a high-altitude Station in the Western Ghats, India - Rohit D. Patil; Subrata Mukherjee; P. P. Leena; Sachin S. Patil; V. Anilkumar; S. M. Sonbawne; S. K. Saha; B. Padmakumari; G. Pandithurai (Aerosol Science and Engineering, 2026)

Understanding the genetics of root system architecture in pigeonpea [Cajanus cajan (L.) Millsp.] - Krishna B. Gaiwal; Shruthi H. Belliappa; Naresh Bomma; Satheesh Naik; N . Sandhyakishore; Sagar K. Rangari; Ashwini Kalyan; Shivaji P. Mehtre; Anilkumar Vemula; Rahul Bhosale; Manish K. Pandey; Harish Gandhi; et al. (Theoretical and Applied Genetics, 2026)
Key message Field-based phenotyping of root system architectural (RSA) traits in a diversity panel (PI-GAP) of pigeonpea was conducted across three diverse pigeonpea growing environments along with identification of genomic regions associated with these traits through GWAS analysis. Abstract Root system architecture (RSA) plays a crucial role in plant stress tolerance mechanisms serving as the main route for water and nutrient acquisition, while also mediating plant-rhizosphere signalling. In the current study, an attempt was made to understand the genetic variability and genomic regions associated with RSA traits, as a relatively unexplored area of research in pigeonpea. The field-based “Shovelomics” approach was utilized to phenotype eight RSA traits: tap root length (TRL), lateral root length (LRL), number of lateral roots (NRL), stem diameter (SD), root diameter (RD), root angle from first and second lateral roots (RA1 and RA2) and root fresh weight (RFW) at physiological maturity. The pigeonpea international genome-wide association panel (PI-GAP) comprising of 185 genotypes from the reference set and 15 elite genotypes were used in the study. The combined ANOVA revealed significant genetic variance for all RSA traits except for RA2. Genome-wide association study was conducted using the Axiom Cajanus 56 K SNP array , leading to identification of 45 marker trait associations (MTAs) associated with RSA traits in pigeonpea. Multi-locus GWAS models detected six MTAs accounting for 4.84% to 18.73% of the phenotypic variation estimated (PVE) for TRL, 12 MTAs for LRL (4.73–13.92% PVE) and 11 MTAs for NLR (3.03–14.03% PVE value), respectively. Candidate gene analysis revealed genes associated with these traits, including BAG (Bcl-2-Associated athanogene) family molecular chaperone regulator 6 ( CcLG01_17476096 and CcLG01_17476721 ), root cap ( CcLG04_5972718 ) and Protein MAINTENANCE OF MERISTEMS (MAIN) ( CcLG06_8242342 ). These genes were found to have key roles in growth and establishment of roots under stress-related conditions in model crops. Further validation of identified MTAs would provide an opportunity to develop trait-specific markers paving the way for marker-assisted breeding in pigeonpea. Based on RSA traits, pigeonpea genotypes were categorized into deep, spreading and dimorphic root system. These classifications facilitate the phenotypic selection of genotypes for breeding against drought, heat, waterlogging and salinity adaptation. Improved cultivars with an ideal root architecture designed for efficient resource uptake and high yield under diverse environments could help address food security challenges in semi-arid tropics.

Dynamics of Total organic carbon: Partitioning, distribution and controlling processes in the Indian sector of the Southern Ocean during austral summer - Melena A. Soares; V. Venkataramana; R.K. Mishra; P. Sabu; R.K. Naik; Manish Tiwari; N. Anilkumar; R. Mohan; K. Mahalinganathan (Journal of Marine Systems, 2025)

Recurring eddies in the Southern Subtropical and Subantarctic Frontal regions of the Indian sector of the Southern Ocean during austral summer - P. Sabu; S. Cxynna; N.N.S. Vishnu; Nirmala J. Nair; Jenson V. George; N. Anilkumar; Rahul Mohan (Dynamics of Atmospheres and Oceans, 2025)

Editorial Expression of Concern: Edibility and nutrient analysis of Diospyros crumenata Thw. fruit: an additional fruit resource from the Western Ghats, India - Rahul Jose; S. Praveena; C. Anilkumar; P. S. Jothish (Genetic Resources and Crop Evolution, 2025)

Identification of novel QTL for bakanae disease resistance in non-basmati indica rice - Malabika Khan; S. Raghu; Rameswar Prasad Sah; T. P. Muhammed Azharudheen; Debashis Moharana; Sasmita Behera; P. Soumya Mohanty; B. Jeevan; Lambodar Behera; B.C. Marndi; Sanghamitra Samantaray; C. Anilkumar (Cereal Research Communications, 2025)

Nutrient dynamics and biogeochemical processes at the Polar front of Indian sector of the Southern Ocean: Influence of Circumpolar deep water intrusion - Melena A. Soares; R.K. Mishra; P. Sabu; V. Venkataramana; R.K. Naik; A. Sarkar; R. Chacko; N. Anilkumar (Polar Science, 2025)

Unraveling the genetic diversity in selected rice cultivars released in the last 60 years using gene-based yield-related markers - S. P. Mohanty; A. Khan; S. Patra; S. Behera; A. K. Nayak; S. Upadhyaya; D. Moharana; Muhammed Azharudheen T. P.; C. Anilkumar; M. K. Kar; G. Basana Gowda; B. C. Marndi; et al. (Genetic Resources and Crop Evolution, 2025)

Comparative investigation of structural properties and biological applications of chemical and biogenic synthesis of zirconium dioxide (ZrO2) nanoparticles using Passiflora edulis - Preetha S; Anilkumar P; Nisha Jenifar A (Journal of Photochemistry and Photobiology B: Biology, 2025)

Harnessing the power of genomics to develop climate-smart crop varieties: A comprehensive review - K.T. Ravikiran; R. Thribhuvan; C. Anilkumar; Jayanth Kallugudi; N.R. Prakash; Sandeep Adavi B; N.C. Sunitha; Krishnan P. Abhijith (Journal of Environmental Management, 2025)

Novel Ti/rGO@ZnCr LDH derived MMO for photocatalytic conversion of atmospheric elements and organic pollutants into valuable resources - Prabagar Jijoe Samuel; Tenzin Thinley; Divya Vinod; Hosakote Shankara Anusha; Hemanth Vikram P R; Gurupadayya B M; Kotermane Mallikarjunappa Anilkumar; Manickam Selvaraj; Mohammed A. Assiri; Harikaranahalli Puttaiah Shivaraju (Journal of Environmental Chemical Engineering, 2024)

Edibility and nutrient analysis of Diospyros crumenata Thw. fruit: an additional fruit resource from the Western Ghats, India - Rahul Jose; S. Praveena; C. Anilkumar; P. S. Jothish (Genetic Resources and Crop Evolution, 2024)

Integrated approaches for the management of invasive fall armyworm, Spodoptera frugiperda (J. E. Smith) in maize - Gadde Anilkumar; P. LakshmiSoujanya; D. V. Sai Ram Kumar; V. Manoj Kumar; K. R. Yathish; J. C. Sekhar; H. S. Jat (Journal of Plant Diseases and Protection, 2024)

Hydrography of the Southern Ocean fronts – The zooplankton link: A detailed study in the Indian Ocean sector - V. Venkataramana; R.K. Mishra; N. Anilkumar; Melena A. Soares; P. Sabu; A. Sarkar (Progress in Oceanography, 2024)

Focused identification of germplasm strategy (FIGS): a strategic approach for trait-enhanced pre-breeding - N. C. Sunitha; M. D. Prathibha; R. Thribhuvan; B. M. Lokeshkumar; P. S. Basavaraj; H. C. Lohithaswa; C. Anilkumar (Genetic Resources and Crop Evolution, 2024)

Improved CeMnO3 perovskite framework for visible-light-aided degradation of tetracycline hydrochloride antibiotic residue and methylene blue dye - H. S. Anusha; S. Yadav; T. Tenzin; J. S. Prabagar; K. M. Anilkumar; W. Kitirote; H. P. Shivaraju (International Journal of Environmental Science and Technology, 2023)

Assessment of in-house algorithms on re-entry time prediction of uncontrolled space objects - Pooja Dutt; M. Mutyalarao; P. Bhanumathy; T.R. Saritha Kumari; Deepak Negi; A.K. Anilkumar; Abhay Kumar; V. Ashok (Advances in Space Research, 2023)

Interannual variability of surface bio-optical characteristics in the frontal zones of the Indian sector of the Southern Ocean during austral summer - Sudarsana Rao Pandi; Sarat C. Tripathy; S.S. Shaju; P. Minu; Anvita U. Kerkar; C.C. Bajish; N. Anilkumar (Polar Science, 2023)

Sorption behavior studies of Cs and its migration in soil samples around Visakhapatnam, India - Sukanta Maity; P. Sandeep; S. Mishra; C. B. Dusane; D. K. Chaudhary; P. Padma Savitri; J. Sudhakar; Anilkumar S. Pillai; A. Vinod Kumar (Environmental Monitoring and Assessment, 2023)

Unravelling genetic architecture and development of core set from elite rice lines using yield-related candidate gene markers - Rameswar Prasad Sah; Sasmita Behera; Sushant Kumar Dash; T. P. Muhammed Azharudheen; Jitendriya Meher; Awadhesh Kumar; Bishnu Charan Marndi; Meera Kumari Kar; H. N. Subudhi; C. Anilkumar (Physiology and Molecular Biology of Plants, 2022)

Genome-wide association analysis for plant type characters and yield using cgSSR markers in rice (Oryza sativa L.) - T. P. Muhammed Azharudheen; Amrit Kumar Nayak; Sasmita Behera; C. Anilkumar; Bishnu Charan Marndi; Debashis Moharana; Lalan Kumar Singh; Sameer Upadhyay; Rameswar Prasad Sah (Euphytica, 2022)

Recent Freshening, Warming, and Contraction of the Antarctic Bottom Water in the Indian Sector of the Southern Ocean - N Anilkumar; Babula Jena; Jenson V. George; Sabu P; Kshitija S; M Ravichandran (Frontiers in Marine Science, 2021)
High saline and cold Antarctic Bottom Water (AABW) forms around the continental margin of Antarctica that ventilates into the global ocean. To study the recent changes in AABW, we have analyzed the in situ observations collected from Indian Ocean expeditions to the Southern Ocean during 2010, 2011, 2017, 2018, and 2020. A comprehensive analysis of these observations indicated recent freshening, warming, and contraction in the layer thickness of the AABW. Even though the AABW depicted inter-annual variability, it changed to moderately fresher and lighter water mass at the end of the recent decade. The characteristics of AABW exhibited a contraction in its layer thickness (∼50–120 m) during recent years. The water mass showed its freshening (∼0.002) and warming (∼0.04°C) tendency from 2018 to 2020. The recent warming (∼0.3°C) of Circumpolar Deep Water (CDW) near the Prydz Bay suggests enhanced melting of ice shelves. It is hypothesized that the combined influences of onshore intrusion of warm CDW, upper ocean warming, sea ice decline, wind forcing, polynya, and calving events possibly caused the freshening and reduction in the thickness of AABW. The continued changes in the ocean-atmospheric environmental conditions and the subsequent changes in the bottom water characteristics likely influence the global climate, overturning circulation, and the biogeochemical cycle.

Picturing beach erosion and deposition trends using PSInSAR: an example from the non-barred southern west coast of India - K. S. Sajinkumar; H. S. Bincy; E. H. Bouali; T. Oommen; C. L. Vishnu; Y. Anilkumar; K. P. Thrivikramji; S. Keerthy (Wetlands Ecology and Management, 2021)

Temperature and phytoplankton size class biomass drives the zooplankton food web dynamics in the Indian Ocean sector of the Southern Ocean - V. Venkataramana; N. Anilkumar; R. K. Naik; R. K. Mishra; P. Sabu (Polar Biology, 2019)

Overfishing and Climate Drives Changes in Biology and Recruitment of the Indian Oil Sardine Sardinella longiceps in Southeastern Arabian Sea - Vasant Kripa; Kolliyil S. Mohamed; K. P. Said Koya; R. Jeyabaskaran; D. Prema; Shelton Padua; Somy Kuriakose; P. S. Anilkumar; Preetha G. Nair; T. V. Ambrose; A. M. Dhanya; K. S. Abhilash; et al. (Frontiers in Marine Science, 2018)

Moisture rainout fraction over the Indian Ocean during austral summer based on $$^{18}\hbox {O}/{}^{16}\hbox {O}$$ 18 O / 16 O ratios of surface seawater, rainwater at latitude range of 10°N–60°S - K Prasanna; Prosenjit Ghosh; S K Bhattacharya; P Rahul; Kei Yoshimura; N Anilkumar (Journal of Earth System Science, 2018)

A Stochastic Approach to Estimate Distribution of Built-Up Area in Regions with Thick Tree Cover - Bimal Puthuvayi; P. P. Anilkumar (Journal of the Indian Society of Remote Sensing, 2018)

Some methodological approaches to the definition of limiting density for aquaculture of freshwater crayfish fingerlings - A. P. Golubev; A. V. Alekhnovich; O. A. Bodilovskaya; Anilkumar Gopinathan (Aquaculture International, 2017)

Seasonal variability in aerosol, CCN and their relationship observed at a high altitude site in Western Ghats - P. P. Leena; G. Pandithurai; V. Anilkumar; P. Murugavel; S. M. Sonbawne; K. K. Dani (Meteorology and Atmospheric Physics, 2016)

Common and distinct neural effects of risperidone and olanzapine during procedural learning in schizophrenia: a randomised longitudinal fMRI study - Veena Kumari; Ulrich Ettinger; Seoung Eun Lee; Christine Deuschl; Anantha P. Anilkumar; Anne Schmechtig; Philip J. Corr; Dominic H. ffytche; Steven C. R. Williams (Psychopharmacology, 2015)

Variability of fronts, fresh water input and chlorophyll in the Indian Ocean sector of the Southern Ocean - N Anilkumar; JV George; R Chacko; N Nuncio; P Sabu (New Zealand Journal of Marine and Freshwater Research, 2015)
The aim of this study was to understand the variability in the fronts and water masses, and the effect of melt water on the concentration of chlorophyll (Chl a ) in the Indian Ocean sector of the Southern Ocean using hydrographic data collected during the austral summer (February 2010 and 2011). The Southern Subtropical Front (SSTF) and Northern Sub Antarctic Front (SAF1) were found to be further south at 57°30′E than at 47–48°E. This southward shift of the fronts was consistent with the southward meandering (c. 2°) of the Antarctic Circumpolar Current (ACC) core from the western section to the eastern section, which could have been caused by the bottom topography. The intrusion of water masses also differed between the western and eastern transects of the study region as a result of the meandering of the ACC core. Fresh water layer thickness relative to the winter water in 2011 was more compared to that during 2010. This could have been due to the larger amount of sea ice that was present in the winter of 2010, which subsequently melted, resulting in the advection of melt water from the south and west of the study region. In situ observations and satellite data detected a high Chl a concentration (c. 0.38 mg m −3 ) south of the Northern Polar Front (PF1) in 2011, which was caused by this melt water.

Biological response to physical processes in the Indian Ocean sector of the Southern Ocean: a case study in the coastal and oceanic waters - N. Anilkumar; Racheal Chacko; P. Sabu; Honey U. K. Pillai; Jenson V. George; C. T. Achuthankutty (Environmental Monitoring and Assessment, 2014)

Genetic dissection of drought tolerance in chickpea (Cicer arietinum L.) - Rajeev K. Varshney; Mahendar Thudi; Spurthi N. Nayak; Pooran M. Gaur; Junichi Kashiwagi; Lakshmanan Krishnamurthy; Deepa Jaganathan; Jahnavi Koppolu; Abhishek Bohra; Shailesh Tripathi; Abhishek Rathore; Aravind K. Jukanti; et al. (Theoretical and Applied Genetics, 2014)

Low-frequency internal waves and their influence on transmission loss variability - P. V. Hareesh Kumar; A. Raghunadha Rao; K. Anilkumar; M. Padmanabham; K. G. Radhakrishnan (Natural Hazards, 2011)

Internal Tides in the Coastal Waters of NE Arabian Sea: Observations and Simulations - P. V. Hareesh Kumar; S. Lekshmi; P. S. V. Jagadeesh; K. Anilkumar; G. V. Krishnakumar; A. D. Rao (Marine Geodesy, 2010)

Effect of jaggery on the quality and intake levels of maize silage - Ragothaman Venkataramanan; Chirukandoth Sreekumar; Rishipal Anilkumar; P. Selvaraj; Nainar M. Vidhya; Iyue Mathagowder (Tropical Animal Health and Production, 2010)

Biosynthesis of polyhydroxyalkanoates co-polymer in E. coli using genes from Pseudomonas and Bacillus - Reeta Davis; P. K. Anilkumar; A. Chandrashekar; T. R. Shamala (Antonie van Leeuwenhoek, 2008)

Fairweather atmospheric electricity at Antarctica during local summer as observed from Indian station, Maitri - C. Panneerselvam; C. Selvaraj; K. Jeeva; K. U. Nair; C. P. Anilkumar; S. Gurubaran (Journal of Earth System Science, 2007)

Amphotericin B-Gum Arabic Conjugates: Synthesis, Toxicity, Bioavailability, and Activities Against Leishmania and Fungi - K. K. Nishi; M. Antony; P. V. Mohanan; T. V. Anilkumar; P. M. Loiseau; A. Jayakrishnan (Pharmaceutical Research, 2007)

Phytotoxins from Pyricularia grisea and Their Effect on Finger Millet - R. P. Sanmathi Kumar; L Shanthala; T. B. Anilkumar; Sudharshana L (Journal of Plant Biochemistry and Biotechnology, 2006)